Development of dye‐sensitized solar cell using M. philippensis (kamala tree) fruit extract: A combined experimental and theoretical study. (10th August 2021) - Mahapatra, Arup; Kumar, Prashant; Bhansare, Jyoti; Surapaneni, Sri Madhavi; Sen, Anik; Pradhan, Basudev
Summary: In this work, we have extracted natural dye from the pericarp of Mallotus phillipensis (kamala tree) fruit which is commonly found in East Asia. The natural dye extract has been used such a photosensitizer for dye‐sensitized solar cells. Density Functional calculations on one of the major constituent natural dye rottlerin, have been performed to check the properties and applicability of the proposed dye as a photosensitizer and manifested high electron injection efficiency. The best performing device exhibited a power conversion efficiency of 0.55% under 100 mW/cm 2 . This kind of non‐toxic and biodegradable natural dye can easily be extracted from an inedible source using a very low‐cost technique and therefore it can provide the best alternative to the synthetic dye for solar cells. Abstract : The natural dye was extracted from the pericarp of inedible source Mallotus phillipensis fruits and was explored as a photosensitizer in dye‐sensitized solar cell (DSSC) with 0.55% efficiency for the first time. DFT and TDDFT calculations of rottlerin dye, a major component in this extract, were performed which showed high electron injection efficiency. This super low‐cost, easily available natural dye extract can provide an alternative candidate in developing cost‐effective solar cells to address the future energy challenge.